(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of this research was to conduct a brief analysis of the relationship between John Raws’ Theory of Justice and stare decisis, as a possible tool for achieving equitable justice through the coherence of decisions. It used the bibliographical research, through the deductive method, with a multidisciplinary conception. He made a succinct approach to Rawlsian theory, followed by the study of the strength of judicial precedents, ending with the presentation of correspondence between both topics. The research is justifiable in view of the legal uncertainty that has been perceived and felt in the context of the Judiciary crisis, where the greatest yearning is stability, coherence and equality in judicial decisions. Thus, the close relationship between fair justice and the doctrine of judicial precedents was found to be true, both of which aim to ensure uniformity and consistency of decisions in order to ensure a minimum of social equality.